The ALMA Spectroscopic Survey in the Hubble Ultra Deep Field: CO excitation and atomic carbon in star-forming galaxies at z = 1-3 - Boogaard, Leindert A.; Werf, Paul van der; Weiss, Axel; Popping, Gergö; Decarli, Roberto; Walter, Fabian; Aravena, Manuel; Bouwens, Rychard; Riechers, Dominik A.; González-López, Jorge; Smail, Ian; Carilli, Chris; et al. (The astrophysical journal, 2020)
We investigate the CO excitation and interstellar medium (ISM) conditions in a cold gas mass-selected sample of 22 star-forming galaxies at z = 0.46-3.60, observed as part of the ALMA Spectroscopic Survey in the Hubble Ultra Deep Field (ASPECS). Combined with Very Large Array follow-up observations, we detect a total of 34 CO transitions with J = 1 up to 8 (and an additional 21 upper limits, up to J = 10) and 6 and transitions (and 12 upper limits). The CO(2-1) and CO(3-2)-selected galaxies, at and 2.5, respectively, exhibit a range in excitation in their mid-J = 4, 5 and high-J = 7, 8 lines, on average lower than (-brighter) BzK-color- and submillimeter-selected galaxies at similar redshifts. The former implies that a warm ISM component is not necessarily prevalent in gas mass-selected galaxies at . We use stacking and Large Velocity Gradient models to measure and predict the average CO ladders at z < 2 and z ≥ 2, finding and , respectively. From the models, we infer that the galaxies at z ≥ 2 have intrinsically higher excitation than those at z < 2. This fits a picture in which the global excitation is driven by an increase in the star formation rate surface density of galaxies with redshift. We derive a neutral atomic carbon abundance of , comparable to the Milky Way and main-sequence galaxies at similar redshifts, and fairly high densities (≥104 cm−3), consistent with the low-J CO excitation. Our results imply a decrease in the cosmic molecular gas mass density at z ≥ 2 compared to previous ASPECS measurements.